Challenges in the Treatment of a Refractory Testicular Germ Cell Tumor in Young Patients with Imminent Organ Failure—A Case Report - Iuliana Pantelimon; Andra-Maria Stancu; Claudiu Socoliuc; Fikirie Abzait; Irina Balescu; Nicolae Bacalbasa; Cristian Balalau; Laurenţia Nicoleta Galeș; Iulian Brezean (Journal of Mind and Medical Sciences)
Background/Aim: This case report navigates through the challenges of a complex clinical scenario involving germ cell tumors (GCTs), one of the most frequently encountered malignancies in adolescents and young adults. Case report: We present the case of an 18-year-old patient exhibiting atypical clinical manifestations, prompting emergent extensive surgical intervention. Upon admission to the Oncology Department, the adolescent presented with jaundice and dyspnea, being diagnosed with pure non-seminomatous embryonal carcinoma, a poor-risk prognosis group. Based on his prognostic group, the patient should have undergone chemotherapy with a well standardized regimen, but the imminent “liver visceral crisis” did not allow for the standard dose chemotherapy administration, so an adapted regimen of chemotherapy was considered and the full number of cycles was applied after this induction cycle. The treatment journey was protracted, emphasizing the need for early recognition and intervention in such cases. A comprehensive ongoing evaluation, including imagistic examinations and laboratory tests, revealed the presence of extensive refractory disease, which led to urgent treatment. Conclusions: This case provides valuable insights into the management of advanced testicular germ cell tumor in young patients facing imminent organ failure and underlines the importance of interdisciplinary collaboration. Understanding the complexities of this condition can aid in improving patient outcomes and enhancing the quality of care provided.